Community Service and its Learning Values: Perceptions of Undergraduate Pharmacy Students - Yap, Andrea Xin Wei; Er, Hui Meng; Ng, Sook Han; Nadarajah, Vishna Devi (Indian Journal of Pharmaceutical Education and Research, 2022)
Introduction: Service learning is commonly incorporated into the curricula of health professions programmes to provide a platform for students to acquire competencies outside the classroom. The objectives of this study were to explore the perceptions of pharmacy students about their experience in course-based community service activities and their educational impact, as well as the contributing factors for effective implementation. Materials and Methods: Twenty semi-structured interviews were conducted among third- and fourth-year pharmacy students in a Malaysian University. All interviews were audio-recorded and transcribed verbatim. The interviews were stopped when no new theme emerged. The data were analysed using a thematic analysis approach. Results: Pharmacy students perceived community service as an experiential learning activity that enabled them to apply the knowledge and practise the skills that they learned in the classroom in real life situations. They had opportunities to enhance their non-cognitive skills through engagement in projects that were preferably related to pharmacy and aligned with their interest. Allocated time, faculty guidance and peer collaboration were important to maximise the educational values of community service. Assessment and feedback provided by supervisors and peers were useful to improve the team dynamics and help students to identify areas of improvement. Conclusion: Participation in community service activity contributed to professional and personal development of pharmacy students.
Keywords: Pharmacy Students; Community Service; Service Learning; Health Professions; Education; Professional Development